Adverse outcome has a U-shaped relation with acute phase change in insulin sensitivity after ST-Elevation Myocardial Infarction. (1st March 2018) - Moura, Filipe A.; Cintra, Riobaldo; Carvalho, Luiz S.F.; Santos, Simone N.; Modolo, Rodrigo; Munhoz, Daniel B.; Quinaglia e Silva, Jose Carlos; Coelho, Otavio R.; Nadruz, Wilson; Sposito, Andrei C.
Abstract: Background: Although stress hyperglycemia after myocardial infarction (MI) is consistently associated with increased mortality, recent studies suggest that the addition of upstream markers of glucose metabolism may improve risk identification. Hence, our aim was to evaluate the association between insulin sensitivity changes during MI hospitalization and outcomes. Methods: A prospective cohort of 331 consecutive ST-Elevation MI (STEMI) patients without insulin provision therapy was used for the analyses. Blood samples were collected upon admission (D1) and after 5 days (D5) of the inciting event. We measured blood glucose and insulin to estimate insulin sensitivity using the updated Homeostasis Model Assessment (HOMA2S). Patients were assessed for intra-hospital death and major adverse cardiac events (MACE) during follow-up. Results: HOMA2S was 62% ± 52% on D1 and 86% ± 57% on D5 (p < 0.001). Total follow-up was a median of 2 (0.9–2.8) years and found a U-shaped relation between the change in HOMA2S from D1 to D5 (ΔHOMA2S) and major adverse cardiac events (MACE) (p = 0.017). Fully adjusted cox-regression models showed that patients from T1 and T3 were about 2.5 times more prone to suffer from MACE than those in T2. Net Reclassification Index adding ΔHOMA2S as a categorical variable dichotomized as T2 and T1 or T3 to a model of GRACE risk score with glucose D1 yielded a better predictive model (0.184 [95% CI 0.124–0.264]; p = 0.032). Conclusion: A U-shaped curve describes the relation between insulin sensitivity change and MACE during acute phase STEMI and, thus indicating that acute dysglycemia must be appreciated in light of a time spectrum and insulin levels.